Population issues : studies from Uttar Pradesh and Bihar - National Seminar on "Demographic Transition and Development: Issues and Challenges in Uttar Pradesh and Bihar" (2014 : Lucknow, India); Sahoo, Harihar; Ram, Faujdar, 1950-; Paswan, B.; Lhungdim, H.; Govil, Dipti; International Institute for Population Sciences; Sanjay Gandhi Post Graduate Institute of Medical Sciences (Mumbai : International Institute for Population Sciences, 2017)
Contributed papers presented at National Seminar on "Demographic Transition and Development: Issues and Challenges in Uttar Pradesh and Bihar", organized by International Institute for Population Sciences in collaboration with Sanjay Gandhi Post Graduate Institute of Medical Sciences, held from March 11-13, 2014 at Lucknow, India.
Includes bibliographical references.
Keywords: Demographic transition -- India -- Uttar Pradesh; Demographic transition -- India -- Bihar; Uttar Pradesh (India) -- Population -- Congresses; Uttar Pradesh (India) -- Social policy -- Congresses; Bihar (India) -- Population -- Congresses; Bihar (India) -- Social policy -- Congresses